Risk analysis and cybersecurity enhancement of Digital Twins in dairy production - Savchenko, Tetiana; Lutska, Nataliia; Vlasenko, Lidiia; Sashnova, Mariana; Zahorulko, Andrii; Minenko, Sofiia; Ibaiev, Eldar; Tytarenko, Nataliia (Technology audit and production reserves, 2025)
The object of research is technological and technical processes that affect the effectiveness of developing a system with Digital Twins and ensuring cyber security using the example of the dairy industry. The work is aimed at solving the problems in the sector of a comprehensive system for monitoring production processes with the possibility of early detection of deviations and potential threats. This, in turn, can lead to a decrease in product quality and an increase in cyber security risks. During the implementation of the research, Digital Twins of the main technological areas was developed using the example of a dairy enterprise, namely: receiving, apparatus and dietary departments. This approach provides for the collection and analysis of data on production parameters (pasteurization temperature, level in tanks, etc.), and also integrates the results of laboratory control. It was found that technological risks have the greatest impact on the effectiveness of the functioning of production processes, and security risks directly account for 35 % of the total threat structure. This is partly due to one of the main problems in the sector of insufficient data protection and possible external interference, including during cyber attacks. In addition, the analysis identified three risk groups (a total of 13 factors), which further allowed to determine their impact on the efficiency of production as a whole. This, in turn, allowed to draw a preliminary conclusion that the use of cybersecurity risk management strategies reduces the likelihood of technical failures and information threats at an industrial enterprise. The results of modeling Digital Twins of the main technological areas using the example of a dairy enterprise showed that the implementation of strategies from the security risk group increases the efficiency of the project by 4%. The results obtained can be used to increase the level of cybersecurity and monitor production processes in the dairy industry and other agro-industrial sectors. The developed Digital Twins can be integrated into quality and safety management systems for food production, in particular, for enterprises operating in conditions of increased risks of cyber threats.